2011
DOI: 10.1089/nat.2011.0309
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Photosensitizer for Light-Controlled Gene Silencing

Abstract: We here demonstrate for the first time that 5-carboxytetramethylrhodamine (TAMRA) covalently linked to nuclear localization signal (NLS)-conjugated peptide nucleic acids (PNAs) are photosensitizers (PSs) with the capacity to initiate photochemical damage to endocytic membranes, resulting in release of endocytosed material into cytosol. Our results show that TAMRA/PNA/NLS conjugates work as multifunctional molecules by offering cellular uptake, PNA-directed gene silencing, and the possibility for targeting in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The structural DNA-mimic, peptide nucleic acid (PNA) is of interest in its own right as a third generation antisense agent, but has also been widely used as a model for studying cellular (and to a lesser extent in vivo ) delivery modalities 3 , 4 . It has previously been shown that cellular delivery of CPP-PNA conjugates can be enhanced by using PCI, through an auxiliary photosensitizer 5 , 21 – 23 or a covalently conjugated dye 24 , 25 . In the present work, we extend these studies by using fluorophore (Alexa Fluor 488 (AF488), Fluorescein, Alexa Fluor 555 (AF555) and Tetramethylrhodamine (TMR)) octaarginine PNA conjugates.…”
Section: Introductionmentioning
confidence: 99%
“…The structural DNA-mimic, peptide nucleic acid (PNA) is of interest in its own right as a third generation antisense agent, but has also been widely used as a model for studying cellular (and to a lesser extent in vivo ) delivery modalities 3 , 4 . It has previously been shown that cellular delivery of CPP-PNA conjugates can be enhanced by using PCI, through an auxiliary photosensitizer 5 , 21 – 23 or a covalently conjugated dye 24 , 25 . In the present work, we extend these studies by using fluorophore (Alexa Fluor 488 (AF488), Fluorescein, Alexa Fluor 555 (AF555) and Tetramethylrhodamine (TMR)) octaarginine PNA conjugates.…”
Section: Introductionmentioning
confidence: 99%
“…The acidification of late endosomes containing 1 was therefore expected to increase the aggregation state of 1 and further hinder its escape. Based on a small number of previous studies involving rhodamine-conjugated nanoparticles in cell cultures, we speculated that “photochemical internalization” (PCI) could allow for the release of the vesicle-trapped TAMRA-dATP. Previous studies have demonstrated that irradiation of tetramethyl rhodamine at or near its excitation maximum results in the formation of singlet oxygen ( 1 O 2 ) and other reactive oxygen species (ROS), which oxidize and rupture the endosomal membrane. , Aside from potential applications in photodynamic therapy, we speculated that a subtoxic dose of light/ROS would release vesicle-trapped TAMRA-dATP into the cytosol and thereby facilitate its incorporation into DNA.…”
Section: Resultsmentioning
confidence: 99%
“…In an interesting study Bøe and co-workers [163] demonstrated light-induced endosomal release and gene silencing for a PNA oligonucleotide where a photosensitizing molecule was covalently attached to the oligonucleotide. The construct also included a positively charged nuclear localization signal peptide, thus constituting a multi-functional molecule offering cellular uptake, gene silencing, and the possibility for light-induced endosomal escape in one cargo.…”
Section: Pci Mediated Oligonucleotide Deliverymentioning
confidence: 99%
“…Polycations can be used for effecting nucleic acid uptake by conferring a positive charge to the negatively charged nucleic acids so that a polycation/nucleic acid complex can be taken up after electrostatic interaction with the negatively charged cell surface. This is a general uptake mechanism that works very well in combination with PCI with many types of nucleic acids ranging from PNAs conjugated to positively charged amino acids [163,217] thorough poly-amino acid mediated delivery of plasmids and mRNA [159,166], to adenovirus coated with polycations [208]. To the extent that the employed polycations are not able to induce a "proton sponge" effect, such systems will often have very low gene delivery efficiency on their own, meaning that PCI can be used to literally turn delivery on, with enhancement factors up to >100 times being observed [85,190].…”
Section: Considerations Regarding the Use Of Pci To Enhance The Theramentioning
confidence: 99%
See 1 more Smart Citation